Ferulic acid esterases for effective processing of plant carbohydrates - Crepin, Valérie (2003)
Feruloyl esterases (E.C. 3.1.1.73), a subclass of the carboxylic acid esterases (E.C. 3.1.1.1), are able to hydrolyse the ester bond between the hydroxycinnamic acids and sugars present in the plant cell walls, and have been classified as Types A or B based on their substrate specificity for aromatic moieties. They constitute an interesting group of enzymes that have the potential for use over a broad range of applications in the agri-food industries. In order to expand the range of available enzymes, we have examined the production of feruloyl esterases by the filamentous fungi Talaromyces slipitalus and Neurospora crassa. Neurospora crassa has been shown to produce multiple feruloyl esterase activities depending upon the time of fermentation with either sugar beet pulp or wheat bran substrates. A gene identified on the basis of its expression on sugar beet pulp has been cloned and over-expressed in Pichia pasloris. The gene encodes a single domain feruloyl esterase (NcFae-l), which represents the first report of a nonmodular Type-B enzyme and the purified recombinant protein has been shown to exhibit concentration dependent substrate inhibition. The kinetic behaviour of the non-modular enzyme is discussed in terms of the diversity in the roles of the feruloyl esterases in the mobilisation of plant cell wall materials and their respective modes of action. A novel feruloyl esterase (TsF AEC, Type-C feruloyl esterase) that exhibits broad substrate specificity in culture supernatants of Talaromyces slipitalus when grown on sugar beet pulp, has been cloned and over-expressed in Pichiapasloris. Various gene fusions have been constructed to investigate the use of alternative signal peptides by P. pastoris and to produce an authentic feruloyl esterase featuring the N-terminal sequence determined for the native enzyme. It has been demonstrated that additional amino acids at the N-terminus of the FAEC sequence do not influence the catalytic capacity of the enzyme, and that the nature of the signal sequence does not appreciably alter the yield of the secreted enzyme. NcFae-l and TsF AEC contain internal peptide sequences that correspond with the consensus motif G-X-S-X-G that contains the catalytic serine nucleophile conserved in the esterase enzyme supcrfamily. The serine residues at the centre of these peptide motifs have been independently mutated and the corresponding enzymes overexpressed in P. pastoris to identify essential serine residues as candidate nucleophiles responsible for catalysing the enzymatic reaction. Based on activity profile data and supported by the characterisation of a recombinant Type-D feruloyl esterase from N. crassa, a feruloyl esterase sub-classification is proposed and discussed in terms of the evolutionary relationships existing between carbohydrate esterases.